IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN BUDAYA RELIGIUS DI SDN SUKALUYU 2 CIANJUR - Pia Nuraripah (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2022)
Religious culture in general is only used as an object of formality in educational institutions, so that it does not actualize the essence of the role of religious culture. In fact, the existence of religious culture is not only a mere formality but as the formation of a perfect personality through worship to the Creator. SDN Sukaluyu 2 is one of the educational institutions located in Sukaluyu village that implements religious culture not only as a mere formality, but can increase a sense of devotion and compassion for fellow human beings, both in one paradigm and in different ones. The religious culture programs contained in the Institute are tadarus, lectures and applying 3 S. SDN Sukaluyu 2 has really actualized the substance of religious culture, because it can be seen from the results of interviews with students and religious teachers that religious culture is not only used as a formal object but as a way of piety to the creator and can improve the religious character found in students such as compassion for others without looking at the bekron of humans themselves.